WHITENESS AS DIGITAL IMAGINARY: SJW AS BOUNDARY OBJECT - Brock, André (AoIR Selected Papers of Internet Research, 2015)
The last few years have seen increased public attention to the ways in which misogyny is performed or contested online (Marcotte 2012; Marwick 2013; Rentschler 2014; Herring and Stoerger 2013). Only rarely, however, has race been incorporated into research on these events (Daniels 2015). This paper seeks to extend research into this area by applying the concept of boundary objects (Star and Griesemer 1989; Star 2010; Bowker and Star 1999) to racial ideology as articulated in a video game, Social Justice Warriors, alongside associated online discussions about the game, and video games and race in general. The paper concludes with a discussion of how Whiteness could be ascertained from other digital boundary objects and the importance of deconstructing racial ideology in technocultural research.